Laws in the hospitality industry : the Philippine tourism laws simplified - Cagurangan, Tranquilino R. Jr. (Manila, 2017)
This book is intended for college students and professionals in the tourism and hospitality management industry.
Keywords: Tourist trade- law and regislation- philippines